Volume of a hot water storage tank with full thermal capacity in relation to daily water consumption - Nejranowski, Jerzy; Szaflik, Władysław (Instal, 2022)
The paper determines the relationship between the capacity of a hot water storage tank with full thermal and daily water consumption. For this purpose, measurements of water consumption distribution during a day for eight buildings in periods exceeding 30 days were used. The measurements show that the average volume of hot water storage tank (HWST) with full thermal capacity and of the daily hot water consumption depend only slightly on the number of residents and virtually do not change with its growth (the size of the installation). It was found that there is a clear correlation between daily hot water consumption in the building and the required volume of HWST at full thermal capacity. The linear relationship between water consumption in the building and the required volume of HWST at full thermal capacity has been determined. Results allow to determine the required volume of the HWST in buildings with different numbers of residents at hot water consumption with a different probability of exceeding and at assuming a determined unit hot water consumption.